The Day of the Lord in Zephaniah 1:1–18: From Prophetic Judgment to Contemporary Ecclesial Understanding - Stefani Gracia Runtukahu; Helen Gratia Masambe (Program Pascasarjana UKIM, 2026)
This study examines the theological meaning of the Day of the Lord in Zephaniah 1:1–18 and its relevance to the contemporary understanding of the congregation of GMIM Moria Girian Indah, Bitung XIII District. Employing a qualitative approach with historical-critical hermeneutics, the research analyzes the historical context, literary features, and theological message of the prophetic text, complemented by field data from the congregation. The findings reveal that the congregation predominantly interprets the Day of the Lord in an eschatological sense, emphasizing future divine judgment while giving limited attention to its historical and ethical dimensions. Exegetical analysis demonstrates that, in Zephaniah, the Day of the Lord also refers to God's historical judgment against Judah's covenant unfaithfulness and serves as a prophetic call to repentance, justice, and covenant fidelity. The study argues that a holistic understanding of the Day of the Lord should integrate its historical, theological, ethical, and eschatological dimensions, encouraging believers to embody repentance, faithful discipleship, and responsible Christian living in the present.